THE EFFECT OF TAKE AND GIVE MODEL ON STUDENTS’ WRITING ESSAY ABILITY - Ainun Fadila (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: The aims of the research is to know: 1) The extent of the application of Take and Give Model in writing essay,2) The extent of the students’ writing essay before and after taught by using Take and Give Model, 3) Whether any significant effect of Take and Give Model on students’ writing essay ability at the twelfth grade students of SMAN 8 Padangsidimpuan. The population in this research is all of the twelfth grade students of SMAN 8 Padangsidimpuan which consist of 94 students. Sample were 24 students which taken by purposive sampling. The research method that used was experimental method.To collect the data the writer used observation sheet and test as an instrument. The mean score of the application Take and Give Model is 3.3 categorized “Very Good”. The result of data analysis show that of ttest 8.28 meanwhile ttable 2.07. It means that ttest is higher than ttable. So, the hypothesis is accepted. It means that there is any significant effect of Take and Give Model on students writing essay ability at the twelfth grade students of SMAN 8 Padangsidimpuan.